Proceedings of the Ocean Drilling Program, 206 Scientific Results 2007
DOI: 10.2973/odp.proc.sr.210.111.2007
|View full text |Cite
|
Sign up to set email alerts
|

Data report: descriptive evaluation of consolidated sedimentary rock structures with X-ray imaging: examples from Site 1276 core samples

Abstract: In order to evaluate X-ray imaging efficacy for observation and description of sedimentary structures in consolidated sedimentary rocks with a computed tomography (CT) scanner, X-ray images obtained during the Ocean Drilling Program Leg 210 cruise and X-ray CT images obtained during postcruise study are compared with split surface digital images of the correlative half-core. Sedimentary structures are clearly to faintly recognized with X-ray images, implying that sedimentary rocks (sandstone, siltstone, and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…X-ray imaging is also efficient for observing dropstones and pebbles. However, Shirai et al (2007) suggested that carbonate rocks might be unsuitable for X-ray imaging because cementation often obscures density contrasts, rendering sedimentary structures homogeneous. When CT numbers are selected in narrower ranges, which is more suitable for observation of sedimentary structures, coral fragments can be clearly distinguished on CT images (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray imaging is also efficient for observing dropstones and pebbles. However, Shirai et al (2007) suggested that carbonate rocks might be unsuitable for X-ray imaging because cementation often obscures density contrasts, rendering sedimentary structures homogeneous. When CT numbers are selected in narrower ranges, which is more suitable for observation of sedimentary structures, coral fragments can be clearly distinguished on CT images (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in point of view are conspicuous in some features. Ashi (1997) and Shirai et al (2007) suggest that some lamina sets drastically change in visibility according to changes in observation direction. 3-D imaging with an X-ray CT system can be observed from any angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper was presented at the 2011 JAPT Geology and Exploration Symposium entitled "Petrophysics -Current applications and challenges for evaluation of rock properties" held in Tokyo, Japan, on June 8, 2011. most of the studies focused on structural and physical property analyses of sediments (Soh et al, 1993;Ashi, 1995;Soh, 1997;Ashi, 1997;Iturrino et al, 2004, Tanaka et al, 2011 , only few others worked on geotechnical properties (Rutledge et al, 1995) , core screening and structural analysis on consolidated sedimentary rocks (Shirai et al, 2007) as well.…”
Section: Value Of X-ray Computed Tomography In the Scienti C Ocean Drmentioning
confidence: 99%